Liquidity Performance Evaluation of Select Steel Companies in India - Descriptive Study - Krishnamoorthi, M. (International Journal of Social Sciences and Management, 2016)
To satisfy the daily needs of an industrial unit, management should think seriously about Liquidity. Working Capital is such of capital that with the help of which a business remains in working condition. It remains live for any business units, Working Capital can be said to be its life. The role of working capital in business is akin to that o heart in the human body. Funds are the life blood of business body. Just as the hart circulates the blood to various organs of body, funds are rotated to various business activities through proper working capital management and any obstruction in the smooth rotation of funds, may causes serious problem in business operations. The generating of income from assets is a very good position in the majority of large and mid-cap companies, but VISA and KALYANI fail to increase its return on assets due to inefficient and ineffective uses of assets, so these companies should take necessary step to increase income by effective utilization of assets. Int. J. Soc. Sc. Manage. Vol. 3, Issue-3: 193-202